2020
DOI: 10.4038/ijms.v7i2.127
|View full text |Cite
|
Sign up to set email alerts
|

Physical and nutritional characteristics of less common traditional rice (<em>Oryza sativa</em> L.) varieties of Sri Lanka

Abstract: Consumption and cultivation of traditional rice varieties have increased considerably in recent yearsdue to the increased prevalence of non-communicable diseases in our country. However, the physical properties and nutritional composition of most traditional rice have not been scientifically studied to a satisfactory level. Therefore, this study determined the physical and nutritional properties of some less common rice varieties namely Pokkali, Murugakayan, Rathdel, Madathawalu, Kuruluthuda, Pachchaperumal, S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Madathawalu is another type of red rice that has traditionally been cultivated in Sri Lanka. The protein and mineral content of these grains is comparatively higher than most other heirloom varieties of rice [23,24]. Studies have shown that the Madathawalu variety contains 12.33±0.02% of moisture, 11.52±0.07% of crude protein, 1.5±0.2% of crude ash, 2.97±0.03% of crude fat, and 84.01±0.3% of total carbohydrates in dry basis [21].…”
Section: Madathawalumentioning
confidence: 96%
“…Madathawalu is another type of red rice that has traditionally been cultivated in Sri Lanka. The protein and mineral content of these grains is comparatively higher than most other heirloom varieties of rice [23,24]. Studies have shown that the Madathawalu variety contains 12.33±0.02% of moisture, 11.52±0.07% of crude protein, 1.5±0.2% of crude ash, 2.97±0.03% of crude fat, and 84.01±0.3% of total carbohydrates in dry basis [21].…”
Section: Madathawalumentioning
confidence: 96%